Memory efficient set partitioning in hierarchical tree (MESH) for wavelet image compression - Farid, Ghani, Prof. Dr.; Abdul Kader; Ekram Khan; R. Badlishah, Ahmad, Prof. Dr. (The Institute of Electronics, Information and Communication Engineers., 2013)
Link to publisher's homepage at http://www.ieice.org/